2019
DOI: 10.3319/tao.2019.01.28.01
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic implications on the 2018 Hualien Earthquake

Abstract: The 2018 Hualien earthquake occurred at the junction of the deformed continental crust of Eurasian plate and the Heping sea basin, where a northeast trending seismic belt exists. In this study, a 3D seismic tomographic inversion is used to investigate the seismogenic structures of the 2018 Hualien earthquake sequence. An earthquake relocation procedure is performed and the focal mechanisms are analyzed to study the faulting behavior. Our results indicate that the source region of the 2018 Hualien earthquake co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…which is buried beneath the Longitudinal Valley fault for the northernmost LV (Shyu et al 2005(Shyu et al , 2006. Wen et al (2019) suggested that the 2018 Hualien earthquake may be associated with a west-dipping blind fault which could reach out to the Heping sea basin and might belong to the Central Range fault. Figure 8 shows the locations of the 2000 Hualien event and its aftershocks, which correlate well with the 2018 Hualien mainshock and its aftershocks.…”
Section: Discussionmentioning
confidence: 99%
“…which is buried beneath the Longitudinal Valley fault for the northernmost LV (Shyu et al 2005(Shyu et al , 2006. Wen et al (2019) suggested that the 2018 Hualien earthquake may be associated with a west-dipping blind fault which could reach out to the Heping sea basin and might belong to the Central Range fault. Figure 8 shows the locations of the 2000 Hualien event and its aftershocks, which correlate well with the 2018 Hualien mainshock and its aftershocks.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the rupture velocity varied from sea to land during the earthquake. Such variation might be associated with local velocity structures, where there is relatively lower velocity structures on land (Huang et al 2014;Wen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…After examining the possible trade-off and ambiguities in solutions, the results show that the main asperity, with strong left-lateral slip, is right underneath Milun Fault where the major damage and the centroid location of regional moment tensor located. Wen et al (2019a) focused on the local background structure of the region and its relation with the 2018 Hualien earthquake. This article presents a comprehensive seismological analysis including 3-D tomographic inversion, earthquake relocation, and focal mechanism determination in the Hualien region.…”
mentioning
confidence: 99%